Mengenal Konsep Mahram Siapa Saja Yang Haram Dinikahi - Riha Datul Aisyah; Nina Novita; Amanda Tri Amelia; Nurul Aini; Wismanto Wismanto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The concept of mahram is one of the pillars of Islamic law that governs relationships among individuals within the context of family and society. The background of this research focuses on the importance of accurate understanding of mahram, especially considering the increasingly complex social interactions in the modern era. The objective of this study is to identify the categories of mahram and to understand their implications for social interactions and marriage. The research method employed is a qualitative approach, using literature analysis and interviews with experts in the fields of religion and family law. The literature study includes recent sources to gain up-to-date perspectives, while interviews are conducted to explore deeper insights regarding the challenges and societal understanding of mahram. The findings indicate that mahram is divided into three main categories: mahram by blood relations, mahram by marriage, and mahram by breastfeeding. Each category has different implications for social interactions, and a good understanding of these boundaries is crucial for maintaining family harmony. The discussion also highlights the modern challenges faced by society regarding the concept of mahram, as well as the necessity for broader education and socialization to enhance awareness among the younger generation. Overall, this research emphasizes the importance of a deep understanding of mahram in creating healthy and harmonious relationships within society, and the need for collaboration among various parties to raise awareness of this concept.